Volume 7B: Structures and Dynamics 2018
DOI: 10.1115/gt2018-75256
|View full text |Cite
|
Sign up to set email alerts
|

Tilting-Pad Journal Bearing in Hybrid Operation: A Numerical and Experimental Investigation

Abstract: Large turbine bearings are usually equipped with hydrostatic jacking mechanisms to separate bearing and shaft during transient start-stop procedures. They are turned off once hydrodynamic operation is reached. In some cases, under severe operating conditions, the hydrostatic oil supply is kept running although the rotor already runs in full speed. The supplied amount of jacking oil is very small compared to the regular oil supply. However, experimental data of a large tilting-pad bearing shows that this hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Still considering the application of hydrostatic jacking mechanisms, Buchhorn et al [21] perform theoretical and experimental investigation varying the hydrostatic pressure, increasing the lubricant viscosity due to the injection of cold oil, decreasing the temperature gradients and, consequently, the thermal pad deformation. The authors concluded that load-carrying increase is not mostly based on the hydrostatic pressure component, since the decreased pad deformations make the largest contribution.…”
mentioning
confidence: 99%
“…Still considering the application of hydrostatic jacking mechanisms, Buchhorn et al [21] perform theoretical and experimental investigation varying the hydrostatic pressure, increasing the lubricant viscosity due to the injection of cold oil, decreasing the temperature gradients and, consequently, the thermal pad deformation. The authors concluded that load-carrying increase is not mostly based on the hydrostatic pressure component, since the decreased pad deformations make the largest contribution.…”
mentioning
confidence: 99%
“…Втім, основний недолік використання води та інших малов'язких водних розчинів для роботи підшипників ковзання полягає в недостатньому гідродинамічному ефекті при малих частотах обертання ротора під час пуску і зупинки турбіни. Тому робота підшипника в режимах пуску і валоповороту, а також при вибігу валопроводу, можлива, зокрема, з використанням гідростатичного підйому ротора [6,7]. При досягненні певної частоти обертання ротора гідропідйом відключається, а гідродинамічний тиск, що розвивається в мастильному шарі підшипника, стає достатнім для створення необхідної товщини мастильного шару, яка забезпечує надійну роботу підшипника [8].…”
Section: авіаційно-космічна техніка і технологія 2022 № 3(179)unclassified
“…Beside their nominal applications, lift-oil devices can be used as a short-term measure if field issues occur. Buchhorn et al [8] report on a reduction of maximum measured pad temperature by up to ∆T = 10 K by activating the hydrostatic assistance system at rated operating conditions of a large turbine tilting-pad journal bearing. The authors relate this behavior to a combined effect of thermo-hydrodynamics and deformation.…”
Section: Introductionmentioning
confidence: 99%